2022
DOI: 10.3389/fpsyt.2022.886297
|View full text |Cite
|
Sign up to set email alerts
|

Computational reinforcement learning, reward (and punishment), and dopamine in psychiatric disorders

Abstract: In the DSM-5, psychiatric diagnoses are made based on self-reported symptoms and clinician-identified signs. Though helpful in choosing potential interventions based on the available regimens, this conceptualization of psychiatric diseases can limit basic science investigation into their underlying causes. The reward prediction error (RPE) hypothesis of dopamine neuron function posits that phasic dopamine signals encode the difference between the rewards a person expects and experiences. The computational fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 182 publications
0
1
0
Order By: Relevance
“…Previous fMRI studies, including our own, have demonstrated that the left DLPFC is involved in decision-making, working memory, and attention processes ( Wesley et al, 2011 , 2014 ; Wesley and Bickel, 2014 ). Fronto-striatal circuits that involve the DLPFC have also been implicated in reinforcement-based computational models of learning and memory ( Lipton et al, 2019 ; Volkow et al, 2019 ; Averbeck and O'Doherty, 2022 ; Liebenow et al, 2022 ). Consistent with a role in CUD, left DLPFC function predicted cannabis versus money choice ( Bedi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous fMRI studies, including our own, have demonstrated that the left DLPFC is involved in decision-making, working memory, and attention processes ( Wesley et al, 2011 , 2014 ; Wesley and Bickel, 2014 ). Fronto-striatal circuits that involve the DLPFC have also been implicated in reinforcement-based computational models of learning and memory ( Lipton et al, 2019 ; Volkow et al, 2019 ; Averbeck and O'Doherty, 2022 ; Liebenow et al, 2022 ). Consistent with a role in CUD, left DLPFC function predicted cannabis versus money choice ( Bedi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%